Pharmacological targeting of MYC-regulated IRE1/XBP1 pathway suppresses MYC-driven breast cancer - Zhao, Na (J Clin Invest, 2018)
The unfolded protein response (UPR) is a cellular homeostatic mechanism that is activated in many human cancers and plays pivotal roles in tumor progression and therapy resistance. However, the molecular mechanisms for UPR activation and regulation in cancer cells remain elusive. Here, we show that oncogenic MYC regulates the inositol-requiring enzyme 1 (IRE1)/X-box binding protein 1 (XBP1) branch of the UPR in breast cancer via multiple mechanisms. We found that MYC directly controls IRE1 transcription by binding to its promoter and enhancer. Furthermore, MYC forms a transcriptional complex with XBP1, a target of IRE1, and enhances its transcriptional activity. Importantly, we demonstrate that XBP1 is a synthetic lethal partner of MYC. Silencing of XBP1 selectively blocked the growth of MYC-hyperactivated cells. Pharmacological inhibition of IRE1 RNase activity with small molecule inhibitor 8866 selectively restrained the MYC-overexpressing tumor growth in vivo in a cohort of preclinical patient-derived xenograft models and genetically engineered mouse models. Strikingly, 8866 substantially enhanced the efficacy of docetaxel chemotherapy, resulting in rapid regression of MYC-overexpressing tumors. Collectively, these data establish the synthetic lethal interaction of the IRE1/XBP1 pathway with MYC hyperactivation and provide a potential therapy for MYC-driven human breast cancers.